Historical materialism and supervenience - Farrelly, Colin (2005)
In this article I put forth a new interpretation of historical materialism titled the supervenient interpretation. Drawing on the insights of analytical Marxism and utilizing the concept of superventence. I advance two central claims. First, that Marx's synchronic materialism maintains that the superstructure supervenes naturally on the economic structure. Second, that diachronic materialism maintains that the relations of production supervene naturally on the forces of production. Taken together, these two these help bring to the fore the central tenets of historical materialism. Furthermore, they help resolve what I call the problem of reductionalism and the problem of verification. - Reproduced.
Keywords: Historical materialism; Marx, Karl; Marxism